Respuesta :
Answer:
3a^2 + 20a + 34
Step-by-step explanation:
(2a + 5)^2 = 4a^2 + 20a + 25
(a +3)(a - 3) = a^2 - 9
Put these two partial answers together.
4a^2 + 20a + 25 -(a^2 -9 ) Remove the brackets.
4a^2 + 20a + 25 - a^2 + 9
4a^2 + 20a + 25 - a^2 + 9
3a^2 + 20a + 34
Answer: 3a² + 20a + 34
Concept:
When doing simplifying expressions, following the PEMDAS method would be easier.
- Parentheses
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
When expanding parentheses, following the FOIL method would be easier.
- First
- Outer
- Inner Last
Solve:
Given expression
(2a + 5)² - (a + 3) (a - 3)
Simplify exponenets
= (2a + 5) (2a + 5) - (a + 3) (a - 3)
Expand parentheses
= 4a² + 10a + 10a + 25 - (a² - 3a + 3a - 9)
= 4a² + 10a + 10a + 25 - a² + 3a - 3a + 9
Combine like terms
= 4a² - a² + 10a + 10a + 3a - 3a + 25 + 9
= 3a² + 20a + 34
Hope this helps!! :)
Please let me know if you have any questions